FRI0079 The Effect of Antirheumatic Therapy Administered in Accordance with "Treat to Target" Principles on Diastolic Dysfunction of the Left and Right Ventricles in Patients with Early Rheumatoid Arthritis During 18-Month Follow-Up. (9th June 2015) - Kirillova, I.; Novikova, D.; Popkova, T.; Korsakova, Y.; Gorbunova, Y.; Markelova, E.; Volkov, A.; Luchihina, E.; Demidova, N.; Kasumova, K.; Vladimirov, S.; Kanonirova, M.; et al.
Abstract : Objectives: To study the effect of antirheumatic therapy administered in accordance with "T2T" principles on diastolic dysfunction of the left (LVDD) and right (RVDD) ventricles in early RA pts during 18-month follow-up. Methods: A total of 66 pts with early RA (ACR/EULAR criteria, 2010) were included in the study: 71% of women, age 56 [46;61] years, disease duration 6 [4;8] months; DAS28 5.3 [5.0;6.2], positive for ACCP (100%), RF (87%), without prior administration of DMARDs and glucocorticoides. All pts underwent blood pressure monitoring (BPM), echocardiography. Methotrexate (MT) therapy was started in all pts with an escalation of the dose up to 30 mg/week subcutaneously. In case of no remission 3 months later, MT was added with biologic therapy (BT): Adalimumab, Certolizumab pegol, Abatacept, Rituximab. After 18 months 29 (44%) pts achieved remission. Antihypertensive therapy was administered in 51 (77%) pts: ACE inhibitors, ARBs, beta-blockers, calcium antagonists, diuretics. Results: At baseline LVDD was detected in 32 (49%) and RVDD in 16 (24%) pts. The LVDD pts were older, in more cases they had AH, CAA, CHD, CAC, TG levels were higher and HDL levels were lower (p<0.05). There were negative correlation between LVDD and ESR (r=-0.3, p<0.03), CRP (r=-0.3, p<0.05), RVDD and CRP (r=-0.3, p<0.03), DAS28 (r=-0.3, p<0.02). After 18 months the incidence rate of LVDD decreased by 7% (from 49% to 42%), RVDD by 5% (from 24% to 17%), p>0.05. In groups of pts receiving MT and MT+BT, the incidence rate of LVDD and RVDD decreased comparably, p>0.05. Two groups of pts were formed. Group 1 included those who achieved remission DAS28<2.6 (n=29), and group 2 included those whose disease activity remained DAS28≥2.6 (n=37). Group 1 showed a decrease in the incidence rate of LVDD by 7% (from 45% to 38%), RVDD by 4% (from 21% to 17%), group 2 - by 5% (from 51% to 46%) and 11% (from 27 to 16%), p>0.05. An improved RVDD correlated with a decrease in CRP, p<0.05. In each group 2 subgroups were isolated depending on the achieved targeted BP values according to physical examination and BPM results (Table 1 ). In pts with DAS28<2.6 and efficient BP control, the normalized diastolic function of LV and RV was observed. In pts without BP control irrespective of the remission achieved, an increased incidence rate of LVDD was observed. In pts without RA remission but with efficient BP control, a decreased incidence rate of LVDD and RVDD was observed as well. Conclusions: A tendency towards a decreased incidence rate of LVDD and RVDD was observed during 18-month therapy of early RA pts in accordance with "T2T" principles. The achieved RA remission and targeted BP values promote an improvement in LV and RV diastolic function. Disclosure of Interest: None declared